2013
DOI: 10.2341/12-140-c
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of and Effect on Tooth Sensitivity of In-office Bleaching Gel Concentrations: A Randomized Clinical Trial

Abstract: A Reis S Kossatz GC Martins AD LoguercioClinical RelevanceFaster bleaching was observed with Whiteness HP Blue 35 (35% hydrogen peroxide) and tooth sensitivity was similar to that found with the lower concentration Whiteness HP Blue 20 (20% hydrogen peroxide). These results cannot be extrapolated to other in-office 35% hydrogen peroxide gels. SUMMARYWith the aim of reducing the side effects of inoffice bleaching agents, less-concentrated hydrogen peroxide (HP) gels have been released by manufacturers. We evalu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
73
0
8

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 101 publications
(85 citation statements)
references
References 21 publications
3
73
0
8
Order By: Relevance
“…3,15,17,19,26 Although some authors reported low effectiveness of in-office bleaching with significant colour rebound soon after bleaching, 4-7 these studies considered the final colour outcome the one produced immediately after bleaching. Teeth tend to appear whiter immediately after bleaching, due to the demineralization caused by the low pH of some bleaching products and the dehydration caused by teeth isolation.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…3,15,17,19,26 Although some authors reported low effectiveness of in-office bleaching with significant colour rebound soon after bleaching, 4-7 these studies considered the final colour outcome the one produced immediately after bleaching. Teeth tend to appear whiter immediately after bleaching, due to the demineralization caused by the low pH of some bleaching products and the dehydration caused by teeth isolation.…”
Section: Discussionmentioning
confidence: 98%
“…We calculated the variation in colour between the two assessment periods (D E) using the formula: D E = [(DL*) 2 + (Da*) 2 + (Db*) 2 ] 1/2 . 15,17 The operator was only considered calibrated when he could get a weighted Kappa of 85% in two consecutive readings of the same teeth in 10 different people.…”
Section: Shade Evaluationmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, Sulieman et al [28] observed that gels with 25, 10, 15, and 5 % H 2 O 2 were capable of achieving the same standard of bleaching (B1, VITA scale) as the gel with 35 % H 2 O 2 by increasing the number of sessions. Other in vivo studies observed a bleaching effect similar to that of the conventional protocol when gels with 15-20 % H 2 O 2 were used, with the advantage of a reduction in the prevalence and intensity of tooth sensitivity [12,13]. Therefore, the use of bleaching gels with low concentrations of H 2 O 2 appears to be an interesting alternative for professional tooth bleaching and is able to be used for teeth with a small enamel and dentin thickness, such as the mandibular incisors, which are more susceptible to the damage resulting from the traditional therapy [7].…”
Section: Discussionmentioning
confidence: 94%
“…The occurrence of damage of such magnitude promotes early pulp tissue aging, since a large number of stem cells, which would be used for odontoblast replacement throughout the life of the dental organ, are lost, thereby reducing the healing capacity of the dentin-pulp complex [20]. Therefore, new parameters for inoffice tooth bleaching have been the target of various contemporary researches, with the aim of minimizing the damage to pulp cells [4,8,11], and the consequent tooth sensitivity related by patients [12,13]. Recently, Soares et al [4] 15 min).…”
Section: Discussionmentioning
confidence: 99%